EVALUATION OF THE EFFECT OF THE COVID-19 PANDEMIC ON THE USE OF SUPPLEMENTS BY INDIVIDUALS OVER THE AGE OF 18 IN THE FERIZAJ DISTRICT - Bucaliu, Ibadete; Isjanovski, Igor; Ismajli, Valza; Ismajli, Veron (Journal of Morphological Sciences, 2023)
The COVID-19 pandemic had a severe impact on the world's population and still remains a serious health problem. Since the beginning of the pandemic, vitamins, minerals and other products known as dietary supplements have received a lot of attention, given their effects on the anti-inflammatory, antioxidant and immune system. The aim of this study is to assess the prevalence of taking DSs during the COVID-19 pandemic and to understand its impact on individuals' beliefs about a healthy life. The paper is a cross-sectional analytical study prepared during April-September 2022. The data were obtained through a questionnaire which was distributed to people aged 18 and older who live in the Ferizaj region. A survey of 500 people was conducted. Half of those surveyed (50.4%) confirm the claim that all supplements, vitamins, minerals, herbs are safe. 50.8% confirm the claim that the effectiveness of nutritional supplements is based on clinical trials. The statement that nutritional supplements are tested before being put on the market is confirmed by 45.2%. 30.7% of those surveyed confirm the claim that all dietary supplements in pharmacies are safe. 83.2% of those surveyed took supplements/additives (vitamins and minerals), 15.2% did not. The largest percentage of 75.6% took vitamin C, followed by 36.8% vitamin D3, 26.2% took group B vitamins, 25.4% Omega 3, 24.0% multi-vitamins and minerals, 21.4% Zinc, 10.6% Potassium and the so-called In total, 53.8% (269) of those surveyed took supplements during the COVID 19 pandemic. According to the dynamics index, a growth rate of 102.3% was registered in relation to the time period before the pandemic with COVID 19. Source of information through which the respondents heard (met) about food supplements (supplements) in the largest percentage before and during the pandemic is from a doctor, health worker (62.2% and 65.6%). 68.8% answered that during the pandemic they took more supplements, and 28.8% did not. Dietary supplement consumption among adults has increased during the COVID-19 pandemic. Keywords : COVID-19, dietary supplements, immunity. https://doi.org/10.55302/JMS2361038b